Daily step counts before, during, and after COVID-19 pandemic: a smartphone-tracking study of university students in Egypt and Saudi Arabia - Mohamed Aly; Mezna AlMarzooqi; Sheref Mohamed; Turki Mohsen Alzahrani; Osama Abdelkarim (BMC, 2023)
Abstract Background COVID-19 pandemic has drastically changed people's lifestyles and daily routines around the world. This study aimed to investigate changes in daily step counts - as an indicator of physical activity - before, during, and after the pandemic among university students in Egypt and Saudi Arabia and to identify regional and gender factors that may have influenced physical activity during these periods. Methods A total of 1273 university students from Egypt (Assiut University and Zagazig University) and Saudi Arabia (Taif University, King Faisal University, and Imam AbdulRahman Bin Faisal University) provided valid data on their daily step counts recorded by a smartphone application (iPhone Health App) from January 2019 to December 2021. The data was divided and averaged based on three periods: the pre-pandemic year (January to December 2019), the first pandemic year (January to December 2020), and the second pandemic year (January to December 2021). Results The results showed a significant decrease in daily steps from pre-pandemic to the first pandemic year, followed by an increase in the second pandemic year. However, daily step counts did not fully recover to pre-pandemic levels in male Egyptian and marginally in male Saudi participants. In both nationalities, female participants did not show a significant difference in daily steps between the pre-pandemic and second-pandemic years. Female Egyptian participants had significantly lower daily step counts than male Egyptian participants, and a gender difference in daily steps was also observed in Saudi female participants in the pre-pandemic and the second pandemic year but not during the first pandemic year. Conclusion These findings outline the need for strategies in Egypt and Saudi Arabia to promote physical activity and reduce sedentary behavior, especially among young women, to mitigate the negative consequences of COVID-19 and meet physical activity guidelines.